2021
DOI: 10.1016/j.mayocp.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Hyperkalemia

Abstract: Hyperkalemia is an electrolyte abnormality with potentially life-threatening consequences. Despite various guidelines, no universally accepted consensus exists on best practices for hyperkalemia monitoring, with variations in precise potassium (K þ) concentration thresholds or for the management of acute or chronic hyperkalemia. Based on the available evidence, this review identifies several critical issues and unmet needs with regard to the management of hyperkalemia. Real-world studies are needed for a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 99 publications
5
106
0
11
Order By: Relevance
“…Moreover, new onset or persistence of mild-to-moderate hyperkalemia (potassium 5.0-6.0 mmol/L) during 12 months of observation significantly increased by 30% the risk of End Stage Renal Disease (ESRD) (4,17,18). It has been suggested that CKD patients adapt to elevated potassium concentrations through modifications in gastrointestinal secretions which may favor intracellular potassium storage, or by increasing insulinmediated intracellular potassium uptake in splanchnic and peripheral muscle tissues (19). On the other hand, relevant are also the related economic costs that double in the presence of persistent hyperkalemia (20).…”
Section: Hyperkalemia In Patients With Ckd Non-dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, new onset or persistence of mild-to-moderate hyperkalemia (potassium 5.0-6.0 mmol/L) during 12 months of observation significantly increased by 30% the risk of End Stage Renal Disease (ESRD) (4,17,18). It has been suggested that CKD patients adapt to elevated potassium concentrations through modifications in gastrointestinal secretions which may favor intracellular potassium storage, or by increasing insulinmediated intracellular potassium uptake in splanchnic and peripheral muscle tissues (19). On the other hand, relevant are also the related economic costs that double in the presence of persistent hyperkalemia (20).…”
Section: Hyperkalemia In Patients With Ckd Non-dialysismentioning
confidence: 99%
“…suboptimal dosing/discontinuation of RAASi among patients with CKD, diabetes or HF compared with those with full RAASi dose (19,47).…”
Section: What Are the Consequences Of Decreasing Or Discontinuing Raas Inhibitors?mentioning
confidence: 99%
“…We must draw attention to the availability of the new potassium binders, patiromer and sodium zirconium cyclosilicate. 9 We would advocate for caution in the use of these potent potassium binders and to always give consideration to the presence of pseudohyperkalemia under appropriate clinical scenarios. [6][7][8]10 We posit that providers managing adult patients with sickle cell disease must be aware of such a phenomenon to avoid the dangers of overtreatment of episodes of pseudohyperkalemia in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations on the monitoring of hyperkalemia in patients with CKD are largely indirect, 1,33 and there is no evidence to inform on the ideal timing or frequency in the hemodialysis setting (Box 2). The association between elevated serum K 1 ($5.5 mmol/L) and hospitalizations has been observed to be stronger when measurements were done on a Friday, rather than a Monday or Wednesday (for patients on a Monday-Wednesday-Friday schedule).…”
Section: Monitoring K 1 In the Hemodialysis Settingmentioning
confidence: 99%
“…22 Not all current guidelines and recommendations on managing hyperkalemia address the use of newer K 1 binders, or how to treat hyperkalemia in the hemodialysis setting. 33 This consensus statement from experienced nephrologists covers current gaps in clinical practice recommendations regarding the management of hyperkalemia in the hemodialysis setting and identifies areas where future research is needed to further reinforce the evidence base supporting these recommendations.…”
Section: Introductionmentioning
confidence: 99%